Work-Related Musculoskeletal Symptoms and Associated Factors Among Academic Staff in Ethiopian Universities. (October 2022) - Zenbaba, Demisu; Sahiledengle, Biniyam; Dibaba, Diriba; Tufa, Tilahun; Mamo, Ayele; Atlaw, Daniel
Background: Work-related musculoskeletal symptoms (WMSs) are common injuries or pains that primarily affect various body structures. It is difficult to estimate the burden of WMSs in developing countries such as Ethiopia due to a lack of evidence, particularly among university academic staff. There is a universal and rapidly growing need for information about WMSs, as this is the main challenge to public health and economic burden. The purpose of this study was to determine the magnitude of work-related musculoskeletal symptoms and their associated factors among academic staff in Ethiopian universities. Methods: From February 2 to March 24, 2021, a web-based cross-sectional study was conducted among 422 academic staff members working in Ethiopian universities. A structured and self-administered Google Form questionnaire was sent and shared with the academic staff via their email addresses, Facebook, and Telegram accounts. Using a p-value of <0.05 and a 95% confidence interval, multivariable logistic regression was used to identify factors associated with the outcome variable. Results: Around 321 (77.2%) of the 416 participants were reported to have work-related musculoskeletal symptoms at least in one part of the body (95% CI: 73.1, 81.5%), with 28.1% reporting lower back pain. Respondents working in second-stage universities (AOR = 7.35, 95% CI 3.21, 16.79), being 44 years old or older (AOR = 7.89, 95% CI 2.10, 21.57), having a Ph.D. (AOR = 7.09, 95% CI 1.50, 17.93), engaging in physical activity (AOR = 3.32, 95% CI 1.43, 7.74), and working on a computer (AOR = 6.89, 95% CI 2. 0.72, 19.15) were the factors associated with work-related musculoskeletal symptoms. Conclusion: Almost three-quarters of academic staff reported work-related musculoskeletal symptoms in this survey. Factors such as university establishment stage, age, educational status, physical activity, and frequent computer use were found to be significantly associated with work-related musculoskeletal symptoms.